INTEGRATION OF CALLIGRAPHY IN QURAN READING AND WRITING: ANALYSIS OF QURAN WRITING SKILLS AMONG ELEMENTARY SCHOOL STUDENTS - Muyassaroh, Iffah; Khamim, Siti; Mubin, Muhammad Nurul (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
This study aims to determine the effectiveness and application of the calligraphy method in learning to read and write the Quran (QRW) at SDN Malangrejo Sleman, which leads to enhanced students' abilities in Quranic learning. This research employs a qualitative descriptive analysis method, with data collected through observation, interviews, and documentation. The results show that teaching Quran reading and writing through calligraphy can foster and develop students' creativity, namely, teaching students to appreciate the art of calligraphy. Therefore, the calligraphy method in QRW learning at SDN Malangrejo Sleman is effective and innovative. The approach, which requires understanding, reading, and writing the Quran correctly, is crucial. It also aims to prevent students from boredom when learning to read and write the Quran and fosters student autonomy. We believe schools and other Islamic education teachers can leverage this research to improve the quality of Quran reading and writing. The findings of this study are expected to prompt teachers and educational institutions to consider the calligraphy method as an alternative approach to learning to read and write the Quran, as it may enhance creativity and students' interest.